Caso de estudio: Diagnóstico empresarial de Casa Andina - Carreño Paliza, Pamela (2022)
This paper has been created to obtain the University degree in Administration. It is structed in six chapters that demonstrate and support the knowledge regards the lessons proposed by the University. Each lesson has relevant value for the development of the Administration career. That is the reason why this sufficiency paper is based in the Casa Andina company, in which I have being working six months, and that has been very important for my professional growth. All answers presented in this paper are orientated and based in Casa Andina Company, through the gained experience of being working in a Company that is permanent directing efforts to positioning itself in a highly competitive market such as the hospitality industry. I believe the effort shown in the develop of this paper will be considerate to obtain the University Degree in Administration, which will allow me to step in the next professional stage.